2005
DOI: 10.1093/cercor/bhj056
|View full text |Cite
|
Sign up to set email alerts
|

Central Signals Rapidly Switch Tactile Processing in Rat Barrel Cortex during Whisker Movements

Abstract: Palpatory movements ('active' touch) are an integral part of tactile sensing. It is known that tactile signals can be modulated in certain behavioral contexts, but it is still unresolved to what degree this modulation is related to movement kinematics and whether it stems from tactile receptors or from central sources. Using awake, head-fixed rats, trained to contact an object, we measured trajectories of muscle-propelled whisker movement precisely and compared tactile responses to contacts thus accomplished w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
101
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 66 publications
15
101
0
Order By: Relevance
“…3 and 9). In light of the results of Hentschke et al (2005), the slow wave we observed, although triggered by the first input volley, might be initiated centrally, propagating back to and within S1. This is consistent with the superficial-to-deeper layer propagation we observed (Fig.…”
Section: Artificial Versus Natural Whiskingmentioning
confidence: 63%
See 1 more Smart Citation
“…3 and 9). In light of the results of Hentschke et al (2005), the slow wave we observed, although triggered by the first input volley, might be initiated centrally, propagating back to and within S1. This is consistent with the superficial-to-deeper layer propagation we observed (Fig.…”
Section: Artificial Versus Natural Whiskingmentioning
confidence: 63%
“…In awake rats, responses in the barrel cortex are modulated during active touch (Krupa et al, 2004;Ferezou et al, 2006). Active whisking increases background activity (Hentschke et al, 2005) and reduces response amplitude for passive but not active touch (Crochet and Petersen, 2006;Ferezou et al, 2006). In our paradigm, initiation of artificial whisking transiently increases background activity (e.g., slow wave in Figs.…”
Section: Artificial Versus Natural Whiskingmentioning
confidence: 81%
“…This is of particular concern as modulation of the whisker sensory system by motor behavior has been observed by a number of researchers (Castro-Alamancos and Oldford 2002;Fanselow and Nicolelis 1999). Furthermore, it is known that the behavioral modification of S1bf to sensory afferents persists even after transection of the infraorbital nerve (Hentschke et al 2006), suggesting that this modulation is generated by the brain and not induced by stimuli. Therefore, the use of ICMS to bypass the sensory periphery was insufficient to address this issue, although, while it has been found that ICMS-evoked oscillations in S1bf vary as a function of behavior (Venkatraman and Carmena 2009), this modulation was observed to occur after the positive and negative features described in this work, during the return to baseline excitation.…”
Section: Discussionmentioning
confidence: 98%
“…Assuming a whisking frequency of ϳ7 Hz and touch times of 50 ms per single whisk (von Heimendahl et al, 2007) these strips of data would be integrated using the short time constant found in the present study and then separated by ϳ100 ms to the next touch time by suppression of signal flow in barrel cortex. In future studies it has to be worked out whether neuronal activity generated by active whisking (Fanselow and Nicolelis, 1999;Hentschke et al, 2006) may recruit memory systems, not available to our passively detecting rats, that in addition integrates information acquired across repetitive whisker strokes.…”
Section: Discussionmentioning
confidence: 99%